Understanding Public Acceptance of Sustainable Transportation Systems: The Roles of Environmental Awareness, Infrastructure Availability, and Policy Trust in Promoting Green Mobility - Arif Fakhrudin; Kifni Yudianto; Maria Valeria Roellyanti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The increasing demand for urban mobility, combined with rapid urbanization and the growing dependence on private vehicles, has intensified environmental and social challenges in urban transportation systems. Issues such as traffic congestion, air pollution, and greenhouse gas emissions have encouraged policymakers to promote sustainable transportation systems as part of broader green mobility strategies. However, the success of sustainable mobility initiatives depends not only on infrastructure development and technological innovation but also on public acceptance and behavioural change. This study aims to analyse the factors influencing public acceptance of sustainable transportation systems in the context of promoting green mobility. Drawing upon insights from environmental behaviour research and transportation policy studies, the study proposes a conceptual framework that examines the influence of environmental awareness, perceived benefits, infrastructure availability, and policy trust on public acceptance of sustainable transportation systems. A quantitative research design was employed using a structured questionnaire distributed to urban residents who regularly engage in daily mobility activities. The collected data were analysed using Structural Equation Modelling (SEM) to evaluate the relationships between the proposed variables. The findings indicate that environmental awareness significantly contributes to individuals’ support for sustainable transportation initiatives. Perceived benefits and infrastructure availability also demonstrate positive relationships with public acceptance, emphasizing the importance of accessible mobility infrastructure and clearly communicated environmental and societal benefits. In addition, policy trust plays a significant role in shaping citizens’ willingness to support sustainability-oriented transportation policies. These findings highlight the importance of integrating behavioural, infrastructural, and institutional strategies in promoting green mobility and accelerating the transition toward sustainable urban transportation systems.